Fluoxetine and Vortioxetine Reverse Depressive-Like Phenotype and Memory Deficits Induced by Aβ1-42 Oligomers in Mice: A Key Role of Transforming Growth Factor-β1 - Torrisi, Sebastiano Alfio; Geraci, Federica; Tropea, Maria Rosaria; Grasso, Margherita; Caruso, Giuseppe; Fidilio, Annamaria; Musso, Nicolò; Sanfilippo, Giulia; Tascedda, Fabio; Palmeri, Agostino; Salomone, Salvatore; Drago, Filippo; et al. (Frontiers in Pharmacology, 2019)
Depression is a risk factor for the development of Alzheimer’s disease (AD), and the presence of depressive symptoms significantly increases the conversion of Mild Cognitive Impairment (MCI) into AD. A long-term treatment with antidepressants reduces the risk to develop AD and different second-generation antidepressants such as selective serotonin reuptake inhibitors (SSRIs) are currently studied for their neuroprotective properties in AD. In the present work, the SSRI fluoxetine and the new multimodal antidepressant vortioxetine were tested for their ability to prevent memory deficits and depressive-like phenotype induced by intracerebroventricular injection of amyloid-β (1-42) (Aβ1-42) oligomers in 2-month-old C57BL/6 mice. Starting from 7 days before Aβ injection, fluoxetine (10 mg/Kg) and vortioxetine (5 and 10 mg/Kg) were intraperitoneally injected daily, for 24 days. Chronic treatment with fluoxetine and vortioxetine (both at the dose of 10 mg/Kg) was able to rescue the loss of memory assessed 14 days after Aβ injection by the passive avoidance task and the object recognition test. Both antidepressants reversed the increase in immobility time detected 19 days after Aβ injection by forced swim test. Vortioxetine exerted significant antidepressant effects also at the dose of 5 mg/Kg. A significant deficit of Transforming Growth Factor-β1 (TGF-β1), paralleling memory deficits and depressive-like phenotype, was found in the hippocampus of Aβ-injected mice in combination with a significant reduction of the synaptic proteins synaptophysin and PSD-95. Fluoxetine and vortioxetine completely rescued hippocampal TGF-β1 levels in Aβ-injected mice as well as synaptophysin and PSD-95 levels. This is the first evidence that a chronic treatment with fluoxetine or vortioxetine can prevent both cognitive deficits and depressive-like phenotype in a non-transgenic animal model of AD with a key contribute of TGF-β1.